Bank Preferences and Government Security Yields - Wolf, Charles R. (Quarterly Journal of Economics, 1971)
Introduction, 283. — I. The portfolio manager's preference for current income and capital gains, 284. — II. Bank preferences and market yields, 289. — III. The values of zi and b derived from market yields, 292. — IV. The values of zj and b derived from a present value analysis, 294. — Conclusion, 301. — Appendix, 301.